2005
DOI: 10.1097/01.bpo.0000151060.85227.67
|View full text |Cite
|
Sign up to set email alerts
|

Residual Shortening After Legg-Calve-Perthes Disease, Focusing on the Response of the Ipsilateral Tibia

Abstract: Residual shortening of the affected limb was measured at skeletal maturity by teleoroentgenograms in 68 patients with Legg-Calve-Perthes disease (LCPD); special attention was paid to the length of the ipsilateral tibia. Of these 68 patients, 38 were treated by abduction orthosis (AO) and 30 by femoral varus osteotomy (FVO). Residual shortening in AO group was significantly greater than that in FVO group. The femoral lengths in both of these groups were similar (12.5 mm in the AO group and 10.1 mm in the FVO gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Grzegorzewski et al [14] stated that varus osteotomy produces more shortening than do other methods of treatment. In contrast, Rowe et al [31] reported less residual shortening in patients treated by varus osteotomy of the proximal femur than in those treated by abduction bracing. However, our findings contrast with those of both of these studies, because we observed similar frequencies of LLD regardless of the patients' age at diagnosis, sex, or the treatment method.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Grzegorzewski et al [14] stated that varus osteotomy produces more shortening than do other methods of treatment. In contrast, Rowe et al [31] reported less residual shortening in patients treated by varus osteotomy of the proximal femur than in those treated by abduction bracing. However, our findings contrast with those of both of these studies, because we observed similar frequencies of LLD regardless of the patients' age at diagnosis, sex, or the treatment method.…”
Section: Discussionmentioning
confidence: 84%
“…Several analyses of the relationship between LCPD and LLD have documented shortening of the affected limb ranging in length from 1 mm to 7 cm [9,14,28,31,35,39]. However, the incidence and predictors of LLD in patients with LCPD remain unclear; furthermore, it is not known whether parameters such as age at diagnosis, sex, type of treatment, and the extent of femoral head involvement can predict the occurrence of LLD.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of the included studies [ 1 , 9 , 10 , 32 , 44 - 61 ] are reported in Multimedia Appendix 1 .…”
Section: Resultsmentioning
confidence: 99%
“…One concern, however, was that it further shortened the affected leg and thus increased the need for the epiphyseal arrest of the normal opposite leg 9, [20][21][22] . It is generally accepted that the amount of the shortening of the affected legs in LCPD depends almost exclusively on the severity of inhibition of endochondral ossification in the proximal femoral growth plate.…”
Section: DI Is Sc Cu Us Ss Si Io On Nmentioning
confidence: 99%
“…In my previous study 20) , our measurements showed that the mean total femoral and tibial shortening was 15.0 mm in the abduction orthosis (AO) group and 9.2 mm in the FVO group (P<0.001). A shortening of 10 mm or more was observed in 66% of the AO group and 40% of the FVO group.…”
Section: DI Is Sc Cu Us Ss Si Io On Nmentioning
confidence: 99%